Unveiling a Governance Analysis Framework for Basic Research in Iran - Zohreh Karimmian; Mostafa Zamanian (Foresight and STI Governance, 2025)
Basic science, as a cornerstone of the national innovation system, has long been at the center of debates on which management approaches are most effective for this activity due to its specific nature that distinguishes it from other types of research. For example, given the long time lag between investment in basic research and the manifestation of economic and social effects from its results, many organizations, especially in the private sector, are reluctant to invest in it. However, insufficient support for basic science becomes a brake on further innovative development and creates the risk of stagnation. This article contributes to the development of these discussions. It considers key concepts of research governance with an emphasis on their application and achieved results in the Iranian context. A comprehensive theoretical framework for analyzing the processes of basic research management in Iran is developed, which can be adapted to similar contexts worldwide. Strategies for improving the alignment of needs and priorities at different funding levels, both operationally and strategically, are proposed. It is concluded that improving the governance of basic science can not only increase the economic returns from research activities, but also bring them into line with societal needs. Appendix